2018
DOI: 10.36104/amc.2018.957
|View full text |Cite
|
Sign up to set email alerts
|

Incidencia y características clínicas de pacientes trasplantados renales con infección y enfermedad por citomegalovirus en un centro de trasplante

Abstract: Introducción: la infección viral más importante postrasplante renal es la infección por citomegalovirus (CMV), hay discrepancia entre centros y países en datos de incidencia de infecciónenfermedad en esta población de pacientes. Diseño: se realiza un estudio observacional analítico, tomando una cohorte retrospectiva de pacientes mayores de 18 años, trasplantados renales de donante vivo o cadavérico entre el 2004 y 2015 con al menos seis meses de seguimiento. Material y métodos: se rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Prophylaxis was used in 45%–58.7% of patients, 22,43,57 and preemptive therapy in 41.3%–56.3% 18,22,25 . Conventional first‐line treatment for the prevention of CMV consisted of either intravenous GCV (5 mg/kg 22,33 ) or oral valganciclovir in both adults and pediatric SOT recipients 6,9,22,30,31,33–34,38,49,50 . Treatment duration ranged between 2 and 3 weeks, with a mean of 15 days in China 58 and 22 days in Brazil 34,38 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Prophylaxis was used in 45%–58.7% of patients, 22,43,57 and preemptive therapy in 41.3%–56.3% 18,22,25 . Conventional first‐line treatment for the prevention of CMV consisted of either intravenous GCV (5 mg/kg 22,33 ) or oral valganciclovir in both adults and pediatric SOT recipients 6,9,22,30,31,33–34,38,49,50 . Treatment duration ranged between 2 and 3 weeks, with a mean of 15 days in China 58 and 22 days in Brazil 34,38 .…”
Section: Resultsmentioning
confidence: 99%
“…(Figure S1). In patients receiving prophylaxis (5 studies), reported rates of CMV infection during the first year post‐SOT were 5.2%, 30 26.0%, 24 45.4%, 31 50.0%, 22 and 50.2% 32 . According to studies conducted in Brazil, India, and South Korea, infection typically appeared after a median of 1–2 months postkidney or postliver transplantation 8,21,25,27,29,32–39 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations